Investment Tax Credits - Robert S. Chirinko (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper examines the history, scope, and types of investment taxcredits (ITC's) implemented in the United States. Changing viewsabout the role of this fiscal policy tool are related to changing viewsabout the structure of the economy and the possibilities forconstructive public policies. The impact of the ITC on economicactivity is reviewed briefly.
Keywords: 330